2022
DOI: 10.3390/rs14215579
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Method for Modeling TEC Regional Temporal-Spatial Map

Abstract: In order to achieve the high-accuracy prediction of the total electron content (TEC) of the regional ionosphere for supporting the application of satellite navigation, positioning, measurement, and controlling, we proposed a modeling method based on machine learning (ML) and use this method to establish an empirical prediction model of TEC for parts of Europe. The model has three main characteristics: (1) The principal component analysis (PCA) is used to separate TEC’s temporal and spatial variation characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Finally, the actual observed values of the training stations were used to predict the TEC of the validation station according to the weight coefficients determined before. Through cross‐validation of modeling stations, RRMSE was used as the evaluation standard to determine the optimal SF (Y. R. Liu et al., 2022). Therefore, SF is chosen as 1.15 in this paper.…”
Section: Validation and Analysismentioning
confidence: 99%
“…Finally, the actual observed values of the training stations were used to predict the TEC of the validation station according to the weight coefficients determined before. Through cross‐validation of modeling stations, RRMSE was used as the evaluation standard to determine the optimal SF (Y. R. Liu et al., 2022). Therefore, SF is chosen as 1.15 in this paper.…”
Section: Validation and Analysismentioning
confidence: 99%
“…In recent years, more and more researches have used the deep learning method, which can reflect TEC variations well and has a better fitting effect on nonlinear data, to establish a TEC prediction model [9] - [23]. For global TEC forecasting, Lee et al [11] proposed a TEC forecast model based on generative adversarial network, and its forecast accuracy was higher than the 1-day forecast product released by CODE Center.…”
Section: Introductionmentioning
confidence: 99%
“…Sivakrishna et al [19] applied bidirectional LSTM algorithm to predict TEC data over Indian region, and illustrated that the potential of bi-LSTM in time series processing is enhanced by having both forward and backward connections. Liu et al [23] presented a machine learning method based on principal component analysis and leastsquare regression to predict TEC over Europe. The above studies have shown that the LSTM model perform well in forecasting ionospheric TEC.…”
Section: Introductionmentioning
confidence: 99%
“…The critical parameters of the F2 layer can be estimated using ionosondes (Yao et al., 2010). These parameters are widely used in satellite, navigation, and high‐frequency communication (e.g., Atac et al., 2009; Kouris et al., 2004; Y. R. Liu et al., 2022b; Moses et al., 2020; Panda et al., 2015; Wang et al., 2022, 2023). The peak height of the ionospheric F2 layer (hmF2) is an essential parameter in the ionospheric F2 layer, which is determined by the height of the ionospheric electron density peak.…”
Section: Introductionmentioning
confidence: 99%